Unraveling the Genetic Architecture of Hepatoblastoma Risk: Birth Defects and Increased Burden of Germline Damaging Variants in Gastrointestinal/Renal Cancer Predisposition and DNA Repair Genes - Aguiar, Talita; Teixeira, Anne; Scliar, Marília O.; Sobral de Barros, Juliana; Lemes, Renan B.; Souza, Silvia; Tolezano, Giovanna; Santos, Fernanda; Tojal, Israel; Cypriano, Monica; Caminada de Toledo, Silvia Regina; Valadares, Eugênia; et al. (Frontiers in Genetics, 2022)
The ultrarare hepatoblastoma is the most common pediatric liver cancer. HB risk is related to a few rare syndromes, and the molecular bases remain elusive for most cases. We investigated the burden of rare damaging germline variants in 30 Brazilian patients with HB. A high frequency of prematurity (20%) and birth defects (37%), especially craniofacial (17%, including craniosynostosis) and kidney (7%) anomalies, was observed. Pathogenic or likely pathogenic variants mapped to 10 cancer predisposition genes (APC, CHEK2, DROSHA, ERCC5, FAH, MSH2, MUTYH, RPS19, TGFBR2 and VHL,) were detected in 33% of the patients, only 40% of them with a family history of cancer. These findings showed a predominance of CPGs with a known link to gastrointestinal/colorectal and renal cancer risk. A remarkable feature was an enrichment of rare damaging variants affecting different classes of DNA repair genes, particularly those known as Fanconi anemia genes. Moreover, several damaging rare variants mapped to genes impacting liver functions were observed. To our knowledge, this is the first comprehensive assessment of rare germline variants in HB patients, contributing to elucidating the genetic architecture of HB risk.